The determination of fibroblast and keratinocyte death types after their transplantation into γ-irradiated porous scaffold in vitro - Y. H. Kot; K. V. Kot; R. A. Kurbanov (Regulatory Mechanisms in Biosystems, 2023)
In the course of radiation therapy, normal cells surrounding the tumor are also irradiated. During and after irradiation, they undergo a series of structural and metabolic changes, which can lead to cell death or transformation. Therefore, when planning and conducting radiation therapy, the effects of radiation on normal cells are taken into account with the aim of predicting and further correcting post-radiation complications, including the development of radiation burns and ulcers. Radiation skin burns are characterized by a prolonged course of the wound healing process, which is accompanied by a sharp decrease in the number of viable cells in the affected tissue from the first hours of irradiation. The type of cell death can significantly impact the effectiveness of radiation therapy and post-radiation complication correction. Therefore, it is important to study the type of their death in irradiated three-dimensional culture on a model of irradiated dermal equivalent, which is widely used today for modeling biological processes. To detect the pathways of cell death, the levels of reactive oxygen species, cell viability, number of cells undergoing autophagy, apoptosis, and necrosis, the content of active caspases 3, 8, and 9 was fluorometrically measured in the irradiated 3D cell culture by laser scanning confocal microscopy. It was determined that the transplantation of fibroblasts and keratinocytes into the irradiated dermal equivalent contributed to an increase in the overall viability of cells of the equivalent and led to a significant decrease in the concentration of free oxygen forms in the irradiated equivalent. Cells within the irradiated equivalent were not evenly distributed in terms of their quantity and viability, with an overall decrease in the cell count over time. A cluster of equivalent cells with significantly higher viability was formed around the transplant. At the same time, the fibroblasts of the transplant were found to be more resistant to the cytotoxic factors of the post-irradiation culture environment compared to keratinocytes. It was demonstrated that non-irradiated dermal equivalent cells predominantly undergo cell death through autophagy, irradiated equivalent cells primarily undergo necrosis, and after the introduction of the transplant, cell death predominantly occurs through apoptosis. In irradiated culture, both with and without transplantation, there is an increase in the content of effector caspase 3. Cells in irradiated culture undergo apoptosis through the mitochondrial mechanism (with a predominance of active caspase 9), while in irradiated culture with the introduction of the transplant, the receptor-mediated mechanism of apoptosis dominates (with a predominance of active caspase 8). The obtained results can be important for the development of new effective methods of therapy for radiation burns, chronic ulcers and wounds of various etiologies.